2001
DOI: 10.1002/app.1681
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight and distribution of copolymer of lignin‐phenol in copolymerization catalyzed by peroxidase

Abstract: The molecular weight and distribution of lignin-cresol polymer in peroxidase-catalyzed copolymerization of lignin with cresol in the reversed micellar system can be controlled by adjusting the surfactant concentration and other factors. The maximal mean molecular weight of copolymer obtained is 1890 kDa. The surfactant sustains chain growth. The cresol and/or polycresol is incorporated into the copolymer, and the thermal property of the copolymer is improved. A correlation for copolymer mean molecular weight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Simona [6] had studied the reactivity of HRP/ H 2 O 2 initiated phenolic in water and obtained a novel 4-phenylphenol ortho dimer. Liu [7] had studied the copolymerization of lignin and phenols with HRP/H 2 O 2 in the organic solution. The results showed that the enzymatic copolymerization have higher reaction rate in organic solution.…”
Section: Introductionmentioning
confidence: 99%
“…Simona [6] had studied the reactivity of HRP/ H 2 O 2 initiated phenolic in water and obtained a novel 4-phenylphenol ortho dimer. Liu [7] had studied the copolymerization of lignin and phenols with HRP/H 2 O 2 in the organic solution. The results showed that the enzymatic copolymerization have higher reaction rate in organic solution.…”
Section: Introductionmentioning
confidence: 99%
“…Simona [3] had studied the reactivity of HRP with water insoluble phenolic compounds, and obtained a novel 4-phenylphenol ortho dimer. Liu and Lv [4] had studied the copolymerization of lignin and phenols with HRP in the system of reverse micro emulsion. The enzymatic copolymerization presented higher reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…Simona [3] had studied the reactivity of Horseradish peroxidase (HRP) with water insoluble phenolic compounds, and obtained a novel 4-phenylphenol ortho dimer. Junhong Liu [4] had studied the copolymerization of lignin and phenols with HRP in the system of reverse micro emulsion. The enzymatic copolymerization presented higher reaction rate.…”
Section: Iintroductionmentioning
confidence: 99%